Hydraulic Fracturing Behavior in Shale with Water and Supercritical CO2 under Triaxial Compression - Jianming He; Yixiang Zhang; Chao Yin; Xiao Li (Geofluids)
Comparing to the water fracturing fluid regularly used in the hydraulic fracturing operation, supercritical CO2 (SC-CO2) as a promising nonaqueous fracturing fluid has the great potential for the improvement of production and protection of shale reservoir. This paper presents an experimental study of the mechanical response and fracture propagation of shale fractured using water and SC-CO2 under the different stress status and injection rate. According to the experimental results, SC-CO2 fracturing is more time-consuming due to its compressibility which takes about 20 times more time than hydraulic fracturing using water under the same preset conditions. The breakdown pressure of shale can be affected by not only the anisotropy of itself but also the external factors like injection rate and deviator stress. Similar tendency of the breakdown pressure with the variation of bedding orientation can be observed in both of the fracturing using water and SC-CO2. However, all of the shale specimens fractured using SC-CO2 show smaller breakdown pressure if compared with the shale specimens fractured using water. According to the results of fracture width evolution monitored by circumference during the fracturing, the fracture propping and proper size of the proppant are really important for the hydraulic fracturing.